Peningkatan Proses Kognitif Siswa SD melalui Pembelajaran IPA Berbasis Aktivitas di SDN Dabasah 3 Bondowoso - Galang Wendra Pramudya Putra; Varah Alviah; Ma’rifatul Jannah; Irham Maulana Saputra; Ika Dewi Setyowati; Ahmad Ivan Dzikri Maulana; Deanova Silsilia Fitri Nasyita; Arik Aguk Wardoyo; Agung Nugroho Puspito (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Science learning in elementary schools is often dominated by lecture-based methods, leading to low student engagement and limited conceptual understanding. This issue was identified among 23 fifth-grade students at SDN Dabasah 3 Bondowoso, particularly in the topic of changes in the states of matter. An activity-based science learning approach was implemented, incorporating simple experiments, group discussions, and educational games. Evaluation used pre-tests, post-tests, and Likert-scale questionnaires analyzed descriptively. Results showed significant improvement, with average scores rising from 64.3 to 81.7 (p = 0.001, Cohen's d = 0.82). Students became more actively engaged, confident in expressing opinions, and capable of connecting concepts to real-life phenomena. Activity-based learning effectively enhanced students' cognitive processes, fostering a more meaningful, interactive, and student-centered learning environment.